Dampak Perkembangan Sumber Keuangan Nagari Terhadap Inovasi Program Dan Kegiatan Pembangunan Nagari Di Kabupaten Solok Selatan Tahun 2013-2016 - Syamsurizaldi .; Annisa Aulia Putri; Rozidateno Putri Hanida; Suherdian Antoni (Jurnal Pembangunan Nagari, 2018)
This study aims to determine the development of Nagari financial resources, know the development of innovations in Nagari development programs and activities, and find out the impact of the development of nagari financial resources on the innovation of nagari development programs and activities before and after the enactment of Law No. 6 of 2014 concerning Villages in South Solok Regency. The research method used is qualitative with interview and documentation data collection techniques. Descriptive analysis research type. The findings of this study are: 1) Nagari financial resources have increased by more than 100% in 2015 and 2016 as a result of the implementation of Law Number 6 of 2014 concerning Villages, but the nagari financial independence is very low, because of the small contribution of native nagari income, 2) shopping Nagari for development is still dominated for physical development, and is still lacking for empowerment activities. 3) the improvement of nagari financial resources has not had a significant impact on program planning innovations and nagari development activitie